2013
DOI: 10.1089/ten.tea.2012.0707
|View full text |Cite
|
Sign up to set email alerts
|

45S5-Bioglass®-Based 3D-Scaffolds Seeded with Human Adipose Tissue-Derived Stem Cells Induce In Vivo Vascularization in the CAM Angiogenesis Assay

Abstract: Poor vascularization is the key limitation for long-term acceptance of large three-dimensional (3D) tissue engineering constructs in regenerative medicine. 45S5 Bioglass Ò was investigated given its potential for applications in bone engineering. Since native Bioglass Ò shows insufficient angiogenic properties, we used a collagen coating, to seed human adipose tissue-derived stem cells (hASC) confluently onto 3D 45S5 Bioglass Ò -based scaffolds. To investigate vascularization by semiquantitative analyses, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
3
39
0
3
Order By: Relevance
“…The BGs1:3 sample whose heat treatment was performed up to 700 °C exhibited smooth surfaces and a high dispersion, different to another samples; like the BG1:12 where it can be seen joints formation between spheres after sintering, plus some hollow spheres which collapsed after heat treatment and the same BGs1:3 system generating a coral type structure with a certain level of surface roughness. This set of results corresponds with other works, where the bioglass sintering behavior make particle fusion as common, besides the surface roughness loss below the 800 °C heat treatment, returning the sample roughness and even increasing it, after higher temperature treatments [21,22].…”
Section: Fig 1 Bioglass Dispersion Diameters After Different Heat Tsupporting
confidence: 90%
See 1 more Smart Citation
“…The BGs1:3 sample whose heat treatment was performed up to 700 °C exhibited smooth surfaces and a high dispersion, different to another samples; like the BG1:12 where it can be seen joints formation between spheres after sintering, plus some hollow spheres which collapsed after heat treatment and the same BGs1:3 system generating a coral type structure with a certain level of surface roughness. This set of results corresponds with other works, where the bioglass sintering behavior make particle fusion as common, besides the surface roughness loss below the 800 °C heat treatment, returning the sample roughness and even increasing it, after higher temperature treatments [21,22].…”
Section: Fig 1 Bioglass Dispersion Diameters After Different Heat Tsupporting
confidence: 90%
“…EDS analysis determined a bioglass 45S5 characteristic spectrum [21] in both systems: the native bioglass (BGs1:3) and the silver-doped bioglass (BGsAg1:3). The presence of contamination by precursors (Fig.…”
Section: Bioglass Compositionmentioning
confidence: 99%
“…47 In accordance with these studies, Handel et al showed that minimal medium containing 1% of crushed 45S5 Bioglass®-based scaffolds induced a signicant proliferation of HUVECs. 48 However, these results do not agree with those by Aina et al, who showed that proliferation of endothelial cells from bovine aorta (BAE-1) in 45S5 Bioglass® used as the substrate was lower than that observed using 45S5 BG modied with 5% ZnO (wt%). 49 The authors attributed the lower proliferation rate to the alkaline pH resulting from the sudden release of ions from 45S5 BG.…”
Section: Discussionmentioning
confidence: 56%
“…In respect to the cells, the bone-derived seed cells can easily differentiate into osteoblasts in vitro; the bone, embryonic bone, and new bone are therefore the optimal sources of seed cells for bone tissue engineering [33,34]. However, it is very difficult to harvest, and the in vitro cell number is thus limited each time.…”
Section: Discussionmentioning
confidence: 99%